Molecular typing of methicillin-resistant Staphylococcus aureus (MRSA) strains isolated in two metropolitan areas of São Paulo State, southeast Brazil - Cury, Gisele Gentile; Mobilon, Cristiane; Stehling, Eliana Guedes; Lancellotti, Marcelo; Ramos, Marcelo De Carvalho; Martinez, Roberto [UNESP]; Brocchi, Marcelo; Silveira, Wanderley Dias Da (Brazilian Society of Infectious Diseases, 2009)
One hundred and fifty-one methicillin-resistant z (MRSA) strains have been isolated from patients admitted in tertiary care hospitals in two metropolitan areas (Campinas City and Ribeirão Preto City) in the southeast region of Brazil and analyzed through PCR-based techniques [(PCR amplification of spa, coa, and housekeeping genes (arcC, aroE, gmk, pta, tpi, yqiL)] and further restriction fragment typing of coa and of housekeeping genes. The heterogeneity of spa gene was determined directly by agarose gel electrophoresis migration. The results obtained indicate the existence of three (A, B, C) main clusters. Since the strain distribution in these three clusters is much characteristic, it denotes the existence of three main clones. All strains isolated in Campinas were grouped in clusters A and B, while most of the strains isolated in Ribeirão Preto were grouped in cluster C. This distribution denotes the existence of different founder strains that undergo independent genetic variability. The strains considered representative of the Brazilian Epidemic Clone (BEC) were categorized as cluster A. These results indicate a possible higher variability among Brazilian MRSA strains than currently described and indicate that the techniques herein used can be used as an alternative to Pulsed Field Gel Electrophoresis (PFGE).
Keywords: MRSA; nosocomial; molecular characterization; PCR